The Munich entrepreneurial ecosystem in the health sector: Current state and improvement areas - Alexandra Hanna James (Junior Management Science (JUMS), 2024)
The study explores entrepreneurial ecosystems, which emphasize the impact of regional context on entrepreneurship, with a particular focus on the health sector. Given its innovation and knowledge intensity, coupled with industry-specific challenges, the health sector serves as an ideal case for ecosystem analysis. This research aims to qualitatively assess Munich's health sector entrepreneurial ecosystem and to identify actionable recommendations for enhancement. To this end, 15 interviews with entrepreneurs, venture capitalists, angel investors and support organization members are analyzed through computer-assisted qualitative content analysis. Results reveal strengths in demand, talent, knowledge, and intermediaries, while physical infrastructure, ecosystem leadership, and formal institutions score lower. The study provides concrete improvement ideas in the areas of financial support, incubators and networks, entrepreneurial education, availability of information and industry collaboration. These insights can be used to strengthen and expand Munich's entrepreneurial ecosystem, contributing to economic, societal, and technological advancements.
Keywords: 650; biotechnology; digital health; entrepreneurial ecosystems; entrepreneurship; life science